Proof-of-concept of a 16-week foot muscle specific intervention programme on non-contact anterior cruciate ligament and lateral ankle sprain injury risk : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Sport & Exercise Science at Massey University, Manawatu, Palmerston North, New Zealand - van der Merwe, Carla (Massey University, 2020)
During high-intensity sports where abrupt decelerations and unanticipated changes of direction are prevalent, impaired foot function is thought to play a role in increasing the risk for non-contact anterior cruciate ligament rupture (ACLR) and lateral ankle sprain (LAS) injury. The risk for sustaining an ACLR is linked to increased rearfoot eversion and excessive, dynamic subtalar joint pronation coupled with internal rotation of the shank, leading to a larger knee valgus angle, and increasing anterior cruciate ligament (ACL) strain under high loads. Impaired forefoot stability is linked to larger moment arm lengths around the ankle joint, increasing the risk for lateral ankle sprain (LAS) under high loads. Previous research has shown that dynamic foot function can influence ankle, knee, and hip movement. Increasing forefoot and medial longitudinal arch stiffness modulates the distal-to-proximal transfer of rotational movement in straight-line walking and running as well as low intensity change of direction tasks. Foot stiffness is created by both passive and active structure in the foot. Passive structures include the foot bones and -ligaments and work in conjunction with the plantar fascia to create stiffness and stability. The intrinsic and extrinsic muscles acting on the foot act in synergy to create stiffness actively. However, current prophylactic programmes do not aim to explicitly train the foot muscles. The aim of this project was thus to provide proof of concept for a foot muscle specific training intervention on dynamic foot function, as well as risk factors associated with ACLR and LAS injury. Establishing proof of concept provides valuable information for future large-scale randomised control studies investigating the integration of a foot muscle specific intervention in to ACLR and LAS injury prevention programmes. The overview of the functional anatomy of the foot in Chapter 2 described the bones that form the joints of the foot as well as the muscles that move the bones of the foot. The interaction of the segments of the foot is described as well as the way in which the foot is modelled. The chapter also provided the contextual evidence for exercise selection. Chapter 4 reviewed the literature and highlighted the relationship between dynamic, excessive subtalar joint pronation and rearfoot eversion to internal tibial rotation, the increase in the knee valgus angle and ACL strain. A link between instability of the forefoot and a larger hallux extension range of motion increasing risk for LAS is discussed. The review also discussed the effect of intrinsic and extrinsic foot muscles on movement of the foot segments and general foot function. A hypothesis was formed that a foot muscle specific intervention has the potential to influence dynamic foot function and risk factors associated with ACLR and LAS, supplementing current prophylactic programmes. Current literature does not definitively describe the coupling relationship between the segments of the lower limb nor the coupling between the segments of the foot during high-intensity unanticipated change of direction tasks. It is thus unknown whether training the foot muscles in an attempt to modulate the transfer of rotational forces from distal-to-proximal segments to decrease injury risk, is justified. A modified vector coding technique was adapted to describe and quantify the coordination patterns between the lower limb and foot segments, respectively. In Chapter 5 the literature regarding the modifications to the vector coding technique and its development from the continues relative phase method of describing movement relationship between objects was presented. The coupling relationship between the tri-planar calcaneus and transverse plane rotation of the shank during unanticipated change of direction tasks was described in Chapter 6. A distal-to-proximal coupling relationship between frontal- and transverse plane movement of the calcaneus and transverse plane rotation of the shank was established. The distal-proximal coupling between the calcaneus and shank suggested that shank rotation may be modulated by manipulating the frontal and transverse plane movement of the calcaneus. It thus seems worthwhile to investigate whether training the muscles that act on the foot would manipulate shank rotations and, in this way, decrease the strain on the ACL, reducing ACLR risk. In Chapter 7 the coupling relationship between the foot segments was described as it influences LAS risk. The forefoot was the only point of contact during unanticipated change of direction tasks. Throughout stance, an anti-phase coupling relationship in the form of metatarsal flexion coupled with calcaneus eversion, and metatarsal extension was coupled with calcaneus inversion. These coupling relationships indicated the importance of forefoot function in calcaneus control and potentially LAS risk. In the loading phase, metatarsal inversion was coupled with calcaneus inversion, potentially increasing LAS risk if metatarsal inversion was not limited. At maximum calcaneus inversion- and adduction velocities, both of which are associated with increased risk for LAS, hallux and metatarsal flexion accelerated. The increased forefoot flexion acceleration indicating the importance of the forefoot stiffness in creating forefoot stability, potentially influencing whole foot stiffness and lateral ankle stability during change of direction tasks. As the forefoot provides stiffness the foot is likely to be more stable and the rearfoot segments are free to move and align with the shank, potentially decreasing LAS risk. It seems thus important to investigate whether training the foot muscles will influence LAS risk. The 16-week progressive foot muscle specific intervention program was detailed in Chapter 8. Exercise components, selection and progression was described. The outcomes of the proof-of-concept study revealed that training the muscles acting on the foot show potential to resist the deformation of the medial longitudinal arch (MLA). Resistance to MLA deformation potentially played a role in the observed decrease of the maximum knee valgus angle, and ACLR risk factor, of the training group (TG). LAS injury risk factors, maximum ankle inversion angle and maximum ankle eversion moment arm length were also smaller for the group undergoing the intervention training. The decrease in the maximums of these LAS risk factors was potentially influenced by the increasing stiffness of the metatarsal anterior transverse arch (MetATA), which is likely to increase foot and ankle stability. Guidelines for future randomised controlled trials included variables to consider ensuring the groups are well matched before the intervention. A proposal regarding the methodology and implementation of an injury prevention programme as well as sample size recommendations were outlined. To ensure the groups are well matched before the intervention it would be prudent to match athletes for stance times, peak ground reaction forces (GRF) in addition to sport and body mass index (BMI). During data collection, the approach speed and thus the timing of the unanticipated change of direction task proved difficult to monitor and control, which potentially influenced the kinetic and kinematic outcomes of the pilot study. The TG also had low compliance to training which could have influenced the result of the intervention. Sample size calculations revealed that a sample size of 30 (falling within the recommended size for biomechanical studies) are needed to find significant differences in foot arch and foot segment angle variables. However, a larger number of athletes are needed per group to establish changes to ACLR and LAS risk variables. Functional anatomy and the coupling relationship between the segments of the lower limb and foot segments justified investigating the effect of foot muscle-specific intervention on ACLR and LAS risk factors. The pilot study revealed that training the muscles acting on the foot seem to influence foot function, but the effect on risk factors associated with ACLR and LAS is unclear. Following the guidelines as described in future randomised control trial is necessary to establish the effectiveness of integrating foot muscle-specific exercises into current ACLR and LAS prophylactic programmes.
Keywords: Anterior cruciate ligament; Ankle; Wounds and injuries; Prevention; Sport injuries; Foot; Muscles; Exercise; 420604 Injury prevention